Асфальт: роман / Евгений Гришковец - Гришковец Евгений Валерьевич (Махаон, 2008)
Экземпляры: Ф6 (20160114) / Инвентарный номер: 51634 / Цена: 183.00 / Сис.шифр: Р2 / Авт.знак: Г 85 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6